Characterization, distribution, and virulence of protistan entomopathogen, Mattesia dispora (Sporozoa, Gregarina) in the Indian meal moth, Plodia interpunctella (Lepidoptera: Pyralidae) populations in Turkey - Mustafa Yaman; Tuğba Sağlam; Ömer Ertürk (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background Indian meal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae) is the dominant pest on the stored products throughout the world. As an alternative to chemical insecticides, entomopathogens can be natural suppressors for pest populations. For this reason, the study of entomopathogens existing in the natural population of a pest contributes to the decision-making process of controlling that pest. In the present study, characterization, distribution, and virulence of protistan entomopathogen, the Turkish strain of Mattesia dispora in the Indian meal moth, Plodia interpunctella populations were presented. Results During the microscopic observations, a protistan entomopathogen was found in the populations of P. interpunctella in Turkey. It was identified as the Turkish strain of Mattesia dispora, a neogregarine pathogen. Typical fresh navicular oocysts of the pathogen were 13.28 ± 0.41 (13.1–14.41) μm in length and 7.72 ± 0.51 (6.6–8.54) μm in width (n = 50). Oocysts stained with Giemsa measured 12.32 ± 0.78 (10.88–13.24) μm in length and 7.01 ± 0.26 (6.5–7.43) μm in width. Polar plugs were recognizable clearly by light and electron microscopy, measuring 900 to 1100 nm. The oocyst wall was quite thick, measuring 600 to 800 nm. Each oocyst contained 8 sporozoites. 2.047 dead and 413 living larvae, 932 adults, and 40 pupae, collected from 14 different locations from 2019 to 2021 were examined for the presence of the protistan entomopathogen. In total, 225 of 3.432 P. interpunctella adult and larvae were found to be infected with this pathogen. Total infection occurred as 5.2 for M. dispora. Infection rates by M. dispora were 4.8% for dead larvae, 14.8% for living larvae, and 2.1% for adults. On the other hand, M. dispora infections reached 33% in some populations. M. dispora infections were observed in the seven (50%) of the examined populations. Furthermore, the Turkish strain of M. dispora had a high pathogenic effect against the second/third instar larvae of P. interpunctella. The average mortality rate was 98.33%. Conclusions Little is known about neogregarine infections as a natural suppressing factor in pest populations. The Turkish strain of M. dispora is very common and widespread in the populations of P. interpunctella. Furthermore, it has very high virulence on the P. interpunctella larvae. Such a widespread infection and very high virulence are desirable properties for a biological control agent. The results indicate that M. dispora can be an important natural suppressing protistan entomopathogen in P. interpunctella populations.